Effects of Water, Sanitation, and Hygiene on the School Absenteeism of Basic Level Students in the Government School of Nepal - Sharma, Mohan Kumar; Adhikari, Ramesh (Frontiers in Education, 2022)
Abstract The study assesses the effect of improved Water, Sanitation, and Hygiene (WASH) services on students' absenteeism at Governmental basic schools aged 10-19 years old in Nepal. The study applies ex-post-facto research design within two groups of students: with and without improved school WASH services. The study showed that students from schools with improved WASH services were more likely to be regular in attendance (80%) compared to those without improved (58%), p<0.001. There was an association between students' school absenteeism and the grade of the students, p<0.05. Moreover, students' caste, religion, and grades were also associated with the students' school absenteeism, p<0.001. The analysis further showed students with improved WASH were more likely regular (COR=0.353; 95% CI; 0.256-0.487, p<0.001) than those without improved WASH. This trend held across all demographics. It was significant even after the inclusion of all socio-demographic characteristics and increased rapidly (AOR=0.508; 95% CI; 0.334-0.773, p<0.01). The Brahmin/Chhetri-Terai and Dalit students' were more likely absent (COR=0.315; 95% CI; 0.153-0.648, p<0.01) and (AOR =0.274; 95% CI; 0.139-0.542, p<0.001), respectively than Brahmin/Chhetri-Hill, Janajati, and other castes as well. This study underscores the importance of WASH services at schools to reduce the students' school absenteeism. Access to WASH services with several awareness programs are recommended to reduce absenteeism and increase students' school regularity. Keywords: Effect, water, sanitation, hygiene, student, absenteeism, Nepal